2009
DOI: 10.1002/jbm.a.32451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrostatic pressure on leporine meniscus cell‐seeded PLLA scaffolds

Abstract: Hydrostatic pressure (HP) is an important component of the loading environment of the knee joint. Studies with articular chondrocytes and TMJ disc fibrochondrocytes have identified certain benefits of HP for tissue engineering purposes. However, similar studies with meniscus cells are lacking. Thus, in this experiment, the effects of applying 10 MPa of HP at three different frequencies (0, 0.1, and 1 Hz) to leporine meniscus cell-seeded PLLA scaffolds were examined. HP was applied once every 3 days for 1 h for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Dynamic compression has been previously used to stimulate engineered and native tissues in simple geometries, upregulating ECM production using both meniscal fibrochondrocytes and articular chondrocytes (Aufderheide and Athanasiou, 2006;Gunja and Athanasiou, 2010;Hunter et al, 2004;Kisiday et al, 2004;Kock et al, 2009;Mauck et al, 2007;Zielinska et al, 2009). In this study we wished to design a system to compress an engineered tissue with complex geometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic compression has been previously used to stimulate engineered and native tissues in simple geometries, upregulating ECM production using both meniscal fibrochondrocytes and articular chondrocytes (Aufderheide and Athanasiou, 2006;Gunja and Athanasiou, 2010;Hunter et al, 2004;Kisiday et al, 2004;Kock et al, 2009;Mauck et al, 2007;Zielinska et al, 2009). In this study we wished to design a system to compress an engineered tissue with complex geometry.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been observed that dynamic compression can enhance extracellular matrix (ECM) production (Zielinska et al, 2009) as well as increase the gene expression for collagenase and matrix metalloproteinases (MMPs) (Upton et al, 2003), it should be noted that the native tissue environment can greatly differ from other tissue engineering studies depending on the biomaterial used. Tissue engineering studies have established that ECM production and mechanical properties can be enhanced through dynamic compression using meniscal fibrochondrocyte-seeded discs (Aufderheide and Athanasiou, 2006;Gunja and Athanasiou, 2010;Zielinska et al, 2009) articular chondrocyte-seeded discs (Hunter et al, 2004;Kisiday et al, 2004;Kock et al, 2009;Mauck et al, 2007). Typical loading regimes included compressive strains of 3-20% at frequencies of 0.3-1 Hz over the course of 0.5-14 days.…”
Section: Introductionmentioning
confidence: 99%
“…[58][59][60] Dynamic compression of constructs based on microchanneled scaffolds resulted in aligned cell layers and collagen fibers, 58 whereas hydrostatic pressure combined with TGF-b1 increased collagen and glycosaminoglycan deposition by meniscus cells, ultimately leading to enhanced compressive properties. 45 Cyclic tension specifically stimulated collagen type I mRNA expression and protein synthesis but had no effect on collagen type II, aggrecan, or osteocalcin mRNA levels, resulting in enhanced fibrochondrocyte-like differentiation of bone marrowederived MSCs. 59 Combinatorial modes of mechanical stimulation, including tension-compression loading 60 or perfusion and cyclic compression, 61 were also reported to additively increase matrix production and tissue mechanical properties.…”
Section: Biological Augmentation and Tissue Engineering Approaches Inmentioning
confidence: 96%
“…[40][41][42] At the same time, 3D woven PCL scaffolds have conferred increased biomechanical properties in a composite preparation with cartilage-derived matrix, obviating the need for growth factor augmentation, and may certainly be applied to meniscus restoration. 43,44 Gunja et al [45][46][47][48] have conducted work using nonwoven poly-L-lactic acid scaffolds exploring the positive synergistic effects of bFGF and hypoxia, hydrostatic pressure, and TGF-ß and coculture (chondrocytes and meniscus cells) using in vitro models. Ultimately, it is hoped that cellular infiltration and matrix deposition may restore some of the viscoelastic properties of meniscus tissue in which the fluid phase carries a significant amount of the load.…”
Section: Biological Augmentation and Tissue Engineering Approaches Inmentioning
confidence: 99%
“…Dynamic compression of constructs based on micro-channelled scaffolds resulted in aligned cell layers and collagen fibres (Martinez et al, 2012), while hydrostatic pressure combined with TGF-β1 increased collagen and GAG deposition by meniscus cells, ultimately leading to enhanced compressive properties (Gunja and Athanasiou, 2010). Cyclic tension specifically stimulated collagen I mRNA expression and protein synthesis, but had no effect on collagen II, aggrecan, or osteocalcin mRNA levels resulting in enhanced fibrochondrocyte-like differentiation of bone marrow-derived MSC (Connelly et al, 2010).…”
Section: Bioreactors For Meniscus Engineeringmentioning
confidence: 99%